Evaluating the performance of different thermal indices on quantifying outdoor thermal sensation in humid subtropical residential areas of China - Li, Kunming; Liu, Xiao; Bao, Ying (Frontiers in Environmental Science, 2022)
Considerations of urban microclimate and thermal comfort are necessary for urban development, and a set of guidelines for a comfortable microclimate must be developed. However, to develop such guidelines, the predictive ability of thermal indices for outdoor thermal comfort under different design decisions must be defined. The present study aimed to determine suitable indices for assessing outdoor thermal comfort in humid subtropical residential areas in China. The study demonstrated the results of field surveys focusing on comparing predictions by different thermal indices and the actual thermal sensation votes (TSVs) indicated by interviewees. Three statistical and two qualitative criteria were established to assess the performance of the selected thermal indices in humid subtropical residential areas of China. The empirical thermal comfort index (TSVmodel) had a better correlation with TSVs, while the Universal Thermal Climate Index (UTCI) was the most successful, simulating 29.8% of TSVs. The testability of the other thermal indices was very low, with the correct predictive ability between 16.5% and 24.4%. For all the indices, the systematic errors (RMSEs) were generally higher than the unsystematic errors (RMSEu), indicating that the assessment scales do not adapt to humid subtropical residential areas in China. The RMSEu was approximately 1, owing to the complexity of the outdoor thermal comfort evaluation. In the selected indices, the UTCI reasonably approximated the observed data for this study and was recommended to assess the outdoor thermal comfort for evaluating the thermal comfort level under different design decisions.